2018
DOI: 10.1002/solr.201800177
|View full text |Cite
|
Sign up to set email alerts
|

Interface Engineering in n‐i‐p Metal Halide Perovskite Solar Cells

Abstract: Recent years have witnessed continuous progress in metal halide perovskite (MHP) solar cells with a certified power conversion efficiency (PCE) exceeding 22%. However, the commercialization of MHP solar cells continues to encounter various challenges including stabilization, scalability and repeatability. Of all problems related to MHP materials, interface recombination is the most prominent, resulting in severe PCE loss within a short time. Fortunately, interface engineering has been identified as an efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 139 publications
(199 reference statements)
0
55
0
Order By: Relevance
“…This result proves that the perovskite layers on the different substrates share the same properties. The intensity of the fluorescence emission reflects the efficiency of carrier extraction; a weak fluorescence indicates a fast charge transfer, which reduces the radiative recombination . This phenomenon is the result of a highly precise energy level match and improved electrical conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…This result proves that the perovskite layers on the different substrates share the same properties. The intensity of the fluorescence emission reflects the efficiency of carrier extraction; a weak fluorescence indicates a fast charge transfer, which reduces the radiative recombination . This phenomenon is the result of a highly precise energy level match and improved electrical conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…Different kinds of functional molecules including Lewis acid and base, alkylammonium halide, and wide bandgap and hydrophobic polymers can passivate perovskite surface acting as interfacial modification layers. [ 2,18–27 ] However, it is still difficult to accurately identify defect types including Pb 2+ /halide vacancies, interstitial Pb 2+ /halides, and undercoordinated Pb 2+ /halides for these multicomponent perovskites. [ 11,28–30 ] Therefore, identifying defect types and adopting suitable passivators are crucial not only to boost the efficiency but also to slow down the moisture degradation.…”
Section: Introductionmentioning
confidence: 99%
“…The lifetime of photogenerated charge carriers (electrons and holes) in perovskite is approximately balanced, normally at a timescale of 10–100 ns in multicrystalline perovskite films and >1000 ns in single crystal of perovskite . Under the driving force of concentration gradient or build‐in potential, the photogenerated carriers will diffuse or migrate to the interfaces; furthermore, the carriers will be selectively separated at the interlayers at a typical timescale of <10 ns; afterward, the free carriers will be collected through the interfacial layers at a typical timescale of <10 μs; at the meantime, before the carriers reach the electrodes, interfacial recombination will compete with the positive transportation at a typical timescale of 1–1000 μs, leading to photocurrent and photovoltage losses. In addition, the back charge transfer at the interfaces occurred at a timescale of 1 μs to 1 ms, resulting in photocurrent loss.…”
Section: Importance Of Interfacial Engineering In Pscsmentioning
confidence: 99%
“…The crystallographic stability and the probable crystal structure of halide perovskite can be predicted by Goldschmidt tolerance factor ( t ) and octahedral factor ( μ ), which are defined by the following formulas t = R normalA + R normalX 2 ( R normalB + R normalX ) μ = R B R X where R A , R B , and R X are the ionic radii of A, B cations and X anion, respectively. If the calculated results are located in the range of 0.81 < t < 1.11 and 0.44 < μ < 0.90, halide perovskite is favorable to form a 3D‐crystal structure . It is reported that an ideal cubic structure will be preferably formed when the value of t locates at a narrower range of 0.89–1.0, whereas a less symmetric tetragonal or orthorhombic structure may be presented if the value of t is lower than this range .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation